2017
DOI: 10.1002/ece3.3172
|View full text |Cite
|
Sign up to set email alerts
|

The multigenerational effects of water contamination and endocrine disrupting chemicals on the fitness of Drosophila melanogaster

Abstract: Water pollution due to human activities produces sedimentation, excessive nutrients, and toxic chemicals, and this, in turn, has an effect on the normal endocrine functioning of living beings. Overall, water pollution may affect some components of the fitness of organisms (e.g., developmental time and fertility). Some toxic compounds found in polluted waters are known as endocrine disruptors (ED), and among these are nonhalogenated phenolic chemicals such as bisphenol A and nonylphenol. To evaluate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Leachates of the PVC particles used in this study have been shown to disrupt sea urchin development and to contain harmful chemicals that can be released into sea water ( Rendell-Bhatti et al, 2020 ). Some plastic additives have been linked to changes in developmental time, size and fitness in D. melanogaster ( Quesada-Calderón et al, 2017 ; Chen et al, 2019 ). In the current study, the plastics were added to a semisolid food matrix, and we did not study the possible release of chemicals from the plastics to the food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leachates of the PVC particles used in this study have been shown to disrupt sea urchin development and to contain harmful chemicals that can be released into sea water ( Rendell-Bhatti et al, 2020 ). Some plastic additives have been linked to changes in developmental time, size and fitness in D. melanogaster ( Quesada-Calderón et al, 2017 ; Chen et al, 2019 ). In the current study, the plastics were added to a semisolid food matrix, and we did not study the possible release of chemicals from the plastics to the food.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no differences in sex ratios were found in C. riparius treated with PE particles of equivalent size to the ones used in this study ( Silva et al, 2019 ). Since plastic additives often include endocrine disruptors, which are also known to affect D. melanogaster ( Quesada-Calderón et al, 2017 ; Chen et al, 2019 ), we initially hypothesised that the male/female ratio could be affected by chemical additives in the PVC treatments. However, we also found an effect in the PE treatment, which had no added chemicals, and hence released chemicals may not be the only factor contributing to this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Water contamination induced by nonylphenol (1670.9 μg/L ± 837.6 g/L = mean ± 1 SD of nonylphenol) can impact the health (development time and fertility) of D. melanogaster , especially the stage from pupa to adult and even at the transgenerational level. However, in some cases, flies could develop different strategies to circumvent various stressful environmental factors (Quesada‐Calderón et al, 2017).…”
Section: Invertebrate Modelsmentioning
confidence: 99%
“…Extreme environmental conditions adversely interfere with reproductive performances in ewes and other animals. Severe environmental conditions such as thermal stress, water scarcity, under nutrition, transhumance and nomadism and the presence of endocrine disrupting substances predispose the animals to oxidative stress through excess production of free radical species that undermines their reproductive performance and overall productivity [1,2,9,31,33,84,97,104,116] . Antioxidants have been employed in the amelioration of the adverse effects of severe environmental conditions [112,114] .…”
Section: Introductionmentioning
confidence: 99%